2016
DOI: 10.1051/0004-6361/201527675
|View full text |Cite
|
Sign up to set email alerts
|

The long-wavelength thermal emission of the Pluto-Charon system fromHerschelobservations. Evidence for emissivity effects

Abstract: Thermal observations of the Pluto-Charon system acquired by the Herschel Space Observatory in February 2012 are presented. They consist of photometric measurements with the PACS and SPIRE instruments (nine visits to the Pluto system each), covering six wavelengths from 70 to 500 μm altogether. The thermal light curve of Pluto-Charon is observed in all filters, albeit more marginally at 160 and especially 500 μm. Putting these data into the context of older ISO, Spitzer and ground-based observations indicates t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 68 publications
3
40
1
Order By: Relevance
“…Note that Lellouch et al (2016) have also found a depressed emissivity at these long wavelengths in observations of the Pluto/Charon system. They interpret this depression as due to a combination of surface and subsurface dielectric and particle/ volume scattering rather than from surface roughness effects (which have often been invoked for these and other bodies at the shorter thermal emission wavelengths, and as described above are actually part of the genesis of the beaming factor).…”
Section: Spitzer/herschel/alma Fits and Millimeter Emissivitymentioning
confidence: 68%
“…Note that Lellouch et al (2016) have also found a depressed emissivity at these long wavelengths in observations of the Pluto/Charon system. They interpret this depression as due to a combination of surface and subsurface dielectric and particle/ volume scattering rather than from surface roughness effects (which have often been invoked for these and other bodies at the shorter thermal emission wavelengths, and as described above are actually part of the genesis of the beaming factor).…”
Section: Spitzer/herschel/alma Fits and Millimeter Emissivitymentioning
confidence: 68%
“…Near-Earth asteroids Müller et al (2012) [M12] (101955) Bennu Müller et al (2017) [M13] (308625) 2005 YU55 Müller et al (2017) [M14] (99942) Apophis Müller et al (2017) [M17] (162173) Ryugu Centaurs and transneptunian objects Duffard et al (2014) [D14] 16 Centaurs Fornasier et al (2013) [F13] Kiss et al (2013) [K13] 2012 DR30 Lellouch et al (2010) [L10] (136108) Haumea Lellouch et al (2013) [L13] Lellouch et al (2016) [L16] Pluto+Charon Lim et al (2010) [LIM10] (136472) Makemake, (90482) Orcus Mommert et al (2012) [MM12] 18 plutinos Müller et al (2010) [M10] Vilenius et al (2012) [V12] 19 classical transneptunian objects Vilenius et al (2014) [V14] 18 classical transneptunian objects Vilenius et al (2018) [V18] 1995 SM 55, 2005RR 43, 2003UZ 117, 2003OP 32, 2002TX 300, 1996TO 66, 1999CD 158, 1999 The following parameters are also extracted from the .csv files obtained by these functions: H, JPL radius, albedo, and slope parameter. In those cases when JPL recognizes the target as a comet and not an asteroid, T-mag (Comet's approximate apparent visual total magnitude), M1 (Total absolute magnitude) parameters are extracted and used.…”
Section: Jpl Horizons Datamentioning
confidence: 99%
“…A locally high thermal inertia may indicate a region of larger average particle size or of greater transparency to sunlight. A locally depressed emissivity may also be related to particle size (and therefore subsurface scattering properties) or may indicate a compositional difference resulting in a distinct spectral emissivity or more transparent surface at the ALMA wavelength (e.g., Lellouch et al 2016Lellouch et al , 2017.…”
Section: Fits To Alma Observationsmentioning
confidence: 99%